Comparison of the airflow characteristics and yarn properties between conventional and dual-feed-opening rotor spinning units. Issue 5 (March 2022) - Shi, Qianqian; Wang, Jiang; Zhang, Yuze; Ding, Qian; Akankwasa, Nicholus Tayari; Lin, Huiting; Wang, Jun
In order to explore the differences between conventional and dual-feed-opening rotor spinning units (RSUs), this work compares the airflow characteristics of two RSU models utilizing a computational fluid dynamics simulation model with the accuracy verified by airflow behavior observation and air pressure measurement. The effect of two different opening roller speeds on the airflow field distribution of a dual-feed-opening model is also investigated. In addition, the yarn properties of six pure and blended yarns corresponding to the two RSU models are evaluated. The results reveal that the distributions of airflow velocity vector and air pressure in the two RSU models show a strong similarity under the same boundary conditions. However, the dual-feed-opening model possesses a centrosymmetric and more balanced airflow field distribution compared to the conventional model. In addition, the dual-feed-opening yarns show a superior performance in comparison to the conventional yarns. Furthermore, for the dual-feed-opening model, there are equivalent contributions of two separated opening and fiber transmission systems to the airflow field distribution and yarn formation. Compared to the configuration with the same two opening roller speeds, the dual-feed-opening model configured with two different opening roller speeds obtains an improved blended yarn performance with having few effects on the airflow characteristics. This strength of the dual-feed-opening RSU could facilitate the production of blended and fancy yarns employing the fibers with diverse properties. This study could provide some guidelines for the manufacture of rotor-spun yarns and the future design of RSUs.